2018
DOI: 10.1002/ehf2.12378
|View full text |Cite
|
Sign up to set email alerts
|

The functional consequences of sodium channel NaV1.8 in human left ventricular hypertrophy

Abstract: AimsIn hypertrophy and heart failure, the proarrhythmic persistent Na+ current (INaL) is enhanced. We aimed to investigate the electrophysiological role of neuronal sodium channel NaV1.8 in human hypertrophied myocardium.Methods and resultsMyocardial tissue of 24 patients suffering from symptomatic severe aortic stenosis and concomitant significant afterload‐induced hypertrophy with preserved ejection fraction was used and compared with 12 healthy controls. We performed quantitative real‐time PCR and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
0
39
1
Order By: Relevance
“…While our findings indicate a lack of functional relevance for Na V 1.8 in CMs under physiological conditions, they do not rule out a potential function during pathophysiological situations. Recently, increased SCN10A/Na V 1.8 expression in human ventricular tissue isolated from heart failure and hypertrophic patients as compared to non-failing and healthy myocardium, has been demonstrated [39,40]. Na V 1.8 inhibition with the specific blockers A-803467 and PF-01247324 decreased late I Na magnitude, abbreviated APD and reduced cellular-spontaneous Ca 2+− release and proarrhythmic events in human failing and hypertrophic CMs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…While our findings indicate a lack of functional relevance for Na V 1.8 in CMs under physiological conditions, they do not rule out a potential function during pathophysiological situations. Recently, increased SCN10A/Na V 1.8 expression in human ventricular tissue isolated from heart failure and hypertrophic patients as compared to non-failing and healthy myocardium, has been demonstrated [39,40]. Na V 1.8 inhibition with the specific blockers A-803467 and PF-01247324 decreased late I Na magnitude, abbreviated APD and reduced cellular-spontaneous Ca 2+− release and proarrhythmic events in human failing and hypertrophic CMs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings in healthy, structurally normal hearts and cardiomyocytes, in disease states-such as heart failure and cardiac hypertrophy-a significant and relevant upregulation of SCN10A/Nav1.8 mRNA and protein expression has been observed both in cardiac tissue and in cardiomyocytes and its functional relevance has been verified by blocking experiments (13,14), suggesting that in the diseased, remodeled heart, the neural form Nav1.8 may indeed directly affect the cardiomyocyte's electrical function.…”
mentioning
confidence: 80%
“…SCN10A/Nav1.8 mutations have been identified in Brugada syndrome (11,12). Moreover, recently, it has been demonstrated that SCN10A/Nav1.8 is upregulated in heart failure (13) and cardiac hypertrophy (14), thus contributing to electrical remodeling in diseased hearts. All these studies suggest that SCN10A/Nav1.8 may play a role in arrhythmogenic cardiac diseases.…”
mentioning
confidence: 99%
“…The enhanced CaMKII-mediated Na v 1.5 phosphorylation, therefore, certainly takes part in increasing I Na,late under oxidative stress. Recent studies have found that Na v 1.8 expression is significantly up-regulated, while Na v 1.5 is reduced in human left ventricular hypertrophy (Ahmad et al, 2019) and HF (Dybkova et al, 2018). The Vicious Circle of CaMKII-I Na,late -…”
Section: [Na + ] I Increases In Many Cardiac Pathologiesmentioning
confidence: 99%
“…Targeting Na v 1.8 with specific inhibitors might provide a potential novel approach in the future in antiarrhythmic drug therapy, because recent studies have found that Na v 1.8 expression is significantly up-regulated in human left ventricular hypertrophy (Ahmad et al, 2019) and HF (Dybkova et al, 2018). By using Na v 1.8-specific blockers [either A-803467 (30 nM) or PF-01247324 (1 mM)] the authors managed to reduce I Na,late and APD in these experiments.…”
Section: Non-cardiac Sodium Channel Inhibitors As Potential Antiarrhymentioning
confidence: 99%